2019
DOI: 10.32508/stdjns.v2i1.676
|View full text |Cite
|
Sign up to set email alerts
|

Application of the collective model to determine some rotational bands of 239U nucleus

Abstract: 238U material is component in fuels of nuclear reactor core. Understanding properties and structure of 238U nucleus is necessary before simulating and designing nuclear reactor. Besides that, the study of nuclear reaction is necessary to identify the specific characteristics of nucleus, it is the most effective experimental method up to now. However, in order to explain the properties of nuclear structure, in addition to study of the nuclear reaction, nuclear structure models and its theory must be used. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This plant distributed in India, Thai Lan, Myanmar, Lao, and Vietnam. 1,2 Z. rhetsa is an indispensable herb in Thai and Mong ethnic groups living in Northwest Vietnam, which use young leaves as a spice and fruits as the culinary soul of this region. 1–3 In folk medicine, fruit, stem, or root barks are used to treat diarrhea, malaria, rheumatism, and worms; essential oil of fruits is used as an antibacterial agent and prevention of cholera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This plant distributed in India, Thai Lan, Myanmar, Lao, and Vietnam. 1,2 Z. rhetsa is an indispensable herb in Thai and Mong ethnic groups living in Northwest Vietnam, which use young leaves as a spice and fruits as the culinary soul of this region. 1–3 In folk medicine, fruit, stem, or root barks are used to treat diarrhea, malaria, rheumatism, and worms; essential oil of fruits is used as an antibacterial agent and prevention of cholera.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Z. rhetsa is an indispensable herb in Thai and Mong ethnic groups living in Northwest Vietnam, which use young leaves as a spice and fruits as the culinary soul of this region. 1–3 In folk medicine, fruit, stem, or root barks are used to treat diarrhea, malaria, rheumatism, and worms; essential oil of fruits is used as an antibacterial agent and prevention of cholera. 1 Recent studies found that Z. rhetsa contains alkaloids, lignans, coumarins, triterpenoids, 48 and monoterpenoids in the essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it could be considered that nuclear quadrupole moment gives the opportunity to calculate the deviation of nuclear shape from a sphere. The mathematical development of the modeling ideas [4][5][6][7] is the basis for the collective model which has been particularly successful for A=24, 150<A<190 and A>230.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it could be considered that nuclear quadrupole moment gives the opportunity to calculate the deviation of nuclear shape from a sphere. The mathematical development of the modeling ideas [4][5][6][7] is the basis for the collective model which has been particularly successful for A=24, 150<A<190 and A>230. The collective model could describe both the rotational states and the vibrational states, in molecular spectra, [8][9][10] one could easily see the evidences about three types of electronic excitation [11][12][13] through the electronic transitions, vibrational levels transitions and/or rotational states.…”
Section: Introductionmentioning
confidence: 99%